2018
DOI: 10.1038/s41467-018-04562-5
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution crossover mapping reveals similarities and differences of male and female recombination in maize

Abstract: Meiotic crossovers (COs) are not uniformly distributed across the genome. Factors affecting this phenomenon are not well understood. Although many species exhibit large differences in CO numbers between sexes, sex-specific aspects of CO landscape are particularly poorly elucidated. Here, we conduct high-resolution CO mapping in maize. Our results show that CO numbers as well as their overall distribution are similar in male and female meioses. There are, nevertheless, dissimilarities at local scale. Male and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

25
100
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(125 citation statements)
references
References 61 publications
25
100
0
Order By: Relevance
“…SPO11-oligo sequencing in Arabidopsis and budding yeast has revealed meiotic DSB hotspots located in nucleosome-free regions associated with gene regulatory sequences (Choi et al, 2018;Pan et al, 2011). Crossovers in plants also positively associate with H3K4me3 and histone variant H2A.Z, which show 5′ enrichment at transcribed genes (Choi et al, 2013;Liu et al, 2009;Wijnker et al, 2013;He et al, 2017;Kianian et al, 2018). In budding yeast, H3K4me3 tethers DSB hotspots to the Mer2 axis protein via the COMPASS complex Spp1 subunit, showing how chromatin and axis organization can interact to promote meiotic recombination (Sommermeyer et al, 2013;Acquaviva et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…SPO11-oligo sequencing in Arabidopsis and budding yeast has revealed meiotic DSB hotspots located in nucleosome-free regions associated with gene regulatory sequences (Choi et al, 2018;Pan et al, 2011). Crossovers in plants also positively associate with H3K4me3 and histone variant H2A.Z, which show 5′ enrichment at transcribed genes (Choi et al, 2013;Liu et al, 2009;Wijnker et al, 2013;He et al, 2017;Kianian et al, 2018). In budding yeast, H3K4me3 tethers DSB hotspots to the Mer2 axis protein via the COMPASS complex Spp1 subunit, showing how chromatin and axis organization can interact to promote meiotic recombination (Sommermeyer et al, 2013;Acquaviva et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…This results in new combinations of alleles in the next generation that can generate novel phenotypic variation, which is the raw material for both natural and artificial selection [1][2][3] . In most organisms, the locations of COs along chromosomes do not form a random distribution [4][5][6][7][8][9][10][11] . Thus, the local CO rate governs the types of allelic combinations that can arise through sexual reproduction.…”
Section: Introductionmentioning
confidence: 99%
“…At the genome-wide scale, maize COs form a particular U-shape pattern, with COs increasing strongly toward chromosome ends ( Anderson et al, 2003 ; Li et al, 2015 ; Rodgers-Melnick et al, 2015 ; Kianian et al, 2018 ). Maize chromosomes have rather big pericentromeric heterochromatin regions that cover more than half of them ( Baucom et al, 2009 ; Wei et al, 2009 ).…”
Section: Crossing Over and Polaritymentioning
confidence: 99%
“…Four studies based on next-generation sequencing have mapped recombination events in maize (Table 3 ). Three studies have been published ( Li et al, 2015 ; Rodgers-Melnick et al, 2015 ; Kianian et al, 2018 ). Data from the fourth study was reported in Alina Ott’s Ph.D. dissertation, and a manuscript is in preparation ( Ott, 2017 ).…”
Section: Crossing Over and Polaritymentioning
confidence: 99%